Lambda Calculus.

Lambda Calculus

syntax

E → ID
E → λ ID. E
E → E E
E → (E)
xyz could be x(yz) or xy(z)
λx.yz could be (λx.y)z  or λx.(yz)
E → E E is left assocative:  xyz == (xy)z
λ x.yz == λ x.(yz)
λx.λy.zw == λx.(λy.(zw))

Note: let x = e in e' is nothing but syntactic sugar for

(λ x . e') e

Semantics

Examples

Expl I

(λx.x+1)3 And here's the abstract-syntax tree (where λ is the abstraction operator, and apply is the application operator):

        apply
        /   \
       λ     3
      / \
     x   +
        / \
       x   1

We rewrite the abstract syntax tree by finding applications of functions to arguments, and for each, replacing the formal parameter with the argument in the function body. To do this,

There is only one apply node in our example; the argument is 3, the function is λx.x+1; the formal parameter is x, and the function body is x+1. Here's the rewriting step:

        apply      =>      +
        /   \             / \
       λ     3           3   1
      / \
     x   +
        / \
       x   1

Here's an example with two applications: (λx.x+1)((λy.y+2)3)

        apply         =>   apply     =>  apply   =>  +  =>  6
       /     \             /   \         /   \      / \
      λ       apply       λ     +       λ     5    5   1
     / \       /  \      / \   / \     / \
    x   +     λ    3    x   + 3   2   x   +
       / \   / \           / \           / \
      x   1 y   +         x   1         x   1
               / \
              y   2

OR

apply         =>    +     =>  +   =>  +  =>  6
/     \             / \       / \     / \
λ       apply     apply 1     +   1   5   1
/ \       /  \      / \       / \
x   +     λ    3    λ   3    3    2
/ \   / \       / \
x   1 y   +     y   +
       / \       / \
y   2     y   2

Expl II

Note that the result of rewriting a non-pure lambda expression can be a constant (as in the examples above), but the result can also be a lambda expression: a variable, or an abstraction, or an application. For a pure lambda expression, the result of rewriting will always itself be a lambda expression. Here are some more examples:

(λf.λx.fx)λy.y+1

        apply      =>   λ        =>    λ        λx.x+1
       /     \         / \            / \
      λ       λ       x  apply       x   +
     / \     / \         /   \          / \
    f   λ   y   +       λ     x        x   1
       / \     / \     / \
      x  apply y  1   y   +
         /  \            / \
        f    x          y   1

Note that the result of the rewriting is a function. Also note that in this example, although there are initially two "apply" nodes, only one of them has a lambda node as its left child, so there is only one rewrite that can be done initially.

(λx.λy.x)(λz.z)

           apply            λ         λy.λz.z
          /     \          / \
         λ       λ    =>  y   λ
        / \     / \          / \
       x   λ   z   z        z   z
          / \
         y   x

(λx.λy.xy)(λz.z)

  apply      =>       λ     =>        λ      λy.y
 /     \             / \             / \
λ       λ           y   apply       y   y
/ \     / \             /     \
x   λ   z   z           λ       y
   / \                 / \
  y  apply            z   z
  /     \
 x       y

Currying

>  #include <iostream>
  using namespace std;

  int F(int a, int b, int c) { return a + b + c; }

  int F_curry() {
    auto f = [](int a) {
      return [a](int b) { return [a, b](int c) { return a + b + c; }; };
    };

    return ((f(1))(2))(3);
  }

  int main() {
    cout << F(1, 2, 3) << endl;
    cout << F_curry() << endl;
  }

Problems with the naive rewriting rule

Problem 1

We don't, in general, want to replace all occurrences of x.

To see why, consider the following (non-pure) lambda expression: (λx.(x + ((λx.x+1)3)))2

This expression should reduce to 6;

the inner expression: (λx.x+1)3 takes one argument, the value 3, and adds 1, producing 4. The outer expression is now: (λx.(x + 4))2 i.e., it takes one argument, the value 2, and adds 4, producing 6.

However, if we rewrite the outer application first, using the naive rewriting rule, here's what happens:

  apply
   /\
  λ  2
 / \
x   +                        +
   / \                      / \
 x   apply     =>          2  apply     =>  +    => 5
      / \    (bad              / \         / \
     λ   3   application)     λ   3       2   +
    / \                      / \             / \
   x   +                    x   +           2   1
      / \                      / \
     x   1                    2   1

We get the wrong answer (5 instead of 6), because we replaced the occurrence of x in the inner expression with the value supplied as the parameter for the outer expression.

Problem 2

Consider the (pure) lambda expression

((λx.λy.x)y)z

The expression λx.λy.x should simply return the first argument, so in this case the result of rewriting should be y. However, if we use the naive rewriting rule, replacing all occurrences of the formal parameter x with the argument y, we get: (λy.y)z

and now if we rewrite that expression we get z

i.e., we got the second argument instead of the first one!

This example illustrates what is called the "capture" or "name clash" problem.

Free variable

A variable is free if it does not appear within the body of an abstraction with a metavariable of the same name

x is free in E if:

  1. E = x
  2. E = λ y . E1, where y != x and x is free in E1
  3. E = E1 E2, where x is free in E1 or E2

Bound Variables

Example

Alpha Reduction

To solve Problem 2, we use a technique called alpha-reduction. The basic idea is that formal parameter names are unimportant; so rename them as needed to avoid capture. Alpha-reduction is used to modify expressions of the form "λx.M". It renames all the occurrences of x that are free in M to some other variable z that does not occur in M (and then λx is changed to λz). For example, consider λx.λy.x+y (this is of the form λx.M). Variable z is not in M, so we can rename x to z; i.e., λx.λy.x+y alpha-reduces to λz.λy.z+y

Beta Reduction

Defined by:

(λx. e1) e2 ⇒ e1[e2/x]

where the notation e1[e2/x] denotes the result of substituting e2 for all free occurrences of x in e1.

(lambda z. (z z)) (lambda x. lambda y. (x y)); A: for apply

    A                        A                 λ        λ
                          /     \              /\       /\
   / \                   λ      λ             w  A     w λ
  /   \                  /\     /\               /\     /\
 λ     λ        ==>     x  λ   x  λ    ->        λ w -> y A
 /\   / \                  /\     /\            /\       /\
z  A  x  λ                w  A   y  A          x λ      w y
   / \    /\                  /\    /\           /\
 z   z   y A                 x w    x y         y A
            /\                                    /\
           x  y                                  x y

λw.(λy.wy)

References